Prognostic significance of mean transmitral pressure gradient in degenerative non-rheumatic mitral valve: insights from a vast echocardiographic database. (3rd October 2022) - Massalha, E; Klempfner, R; Maor, E; Beigel, R; Kuperstein, R; Matetzky, S; Beinart, R; Segev, A; Guetta, V; Fefer, P
Abstract: Background: The incidence and prevalence of senile, non-rheumatic mitral valve disease are increasing and there is a renewed interest in new transcatheter structural cardiac interventions intended to treat that valvular disorder. While the severity of rheumatic mitral valve disease can be accurately assessed by echocardiography using various parameters, including mean transmitral pressure gradient, these methods have been questioned for quantifying senile mitral valve disorder and their prognostic significance is still unknown. Aims: The current study aims to document the natural history of patients with elevated senile mean transmitral pressure gradient (MG) and assess its prognostic significance. Methods: A vast institutional echocardiography database was retrospectively analyzed from 2009 to 2020 for all patients aged over 60 years with a detailed echocardiography report with valid measurement of transmitral gradients. Patients with rheumatic valvular disease or who underwent surgical or transcatheter valvular replacement/repair were excluded. All-cause mortality was set to be the primary outcome, and survival models utilizing univariable and adjusted multivariable analysis for various clinical and echocardiographic variables were applied. Results: A total of 5524 patients consisted of the final cohort. They were stratified by the MG into three groups: MG <3 (2914 patients, 53%), 3≤MG<6 (2079 patients, 37.6%) and MG ≥6 mmHg (531 patients, 9.6%). The mean age of the total cohort was 77.2±7.9 years; 60.5% were female, 33.3% with diabetes mellitus, 15.1% with chronic kidney disease, and 14.1% with ischemic heart disease. An Adjusted Cox proportional hazard regression model demonstrated that MG is independently associated with all-cause mortality (adjusted HR 1.04 per 1 mmHg increase, 95% CI 1.02–1.05, p<0.001). Moreover, an elevated MG was associated with a rise in all-cause mortality (HR of 1.15 and 1.4 for patients with 3≤MG<6 and MG ≥6 mmHg, respectively (Fig. 1). Conclusion: The elevated mean transmitral gradient in senile non-rheumatic valves is an independent predictor for all-cause mortality. Interventions and prospective trials intended to mitigate that risk should be needed. Funding Acknowledgement: Type of funding sources: None.